The Effectiveness and Safety of High-Dose Colistin: Prospective Cohort Study. (6th October 2016) - Benattar, Yael Dishon; Omar, Muna; Zusman, Oren; Yahav, Dafna; Zak-Doron, Yael; Altunin, Sergey; Elbaz, Michal; Daitch, Vered; Granot, Michal; Leibovici, Leonard; Paul, Mical
Abstract : All-cause 28-day mortality rates were not significantly different among patients receiving a median daily dose of colistin of 9 million international units (MIU) vs 4 MIU for carbapenem-resistant gram-negative infections, but nephrotoxicity was more frequent with high dosing. Abstract : Background: Optimizing colistin dosing should translate to improved patient outcomes. Methods: We used data from 2 prospective cohort studies performed between 2006 and 2009 and between 2012 and 2015. In the latter period, a new policy of high-dose colistin (9 million international units [MIU] loading dose followed by 9 MIU daily for normal renal function) was introduced in 2 participating hospitals. We included adult inpatients with invasive infections caused by carbapenem-resistant gram-negative bacteria treated with colistin. Our primary exposure variable was colistin dose, dichotomized to high-dose vs other regimens. The primary outcome was 28-day mortality. We generated a propensity score for high-dose colistin and conducted propensity-adjusted multivariable and matched-cohort analyses for mortality. Results: Of 529 consecutive patients fulfilling inclusion criteria, 144 were treated with high-dose colistin and 385 with lower-dose colistin regimens. The median daily dose in the high-dose group was 9 MIU (interquartile range [IQR], 9–9) vs 4 MIU (IQR, 3–6) with other regimens. There were 50 of 144 (34.7%) deaths with high-dose colistin vs 165 of 385 (42.9%) with low-dose colistin ( P = .1). The propensity-adjusted odds ratio (OR) for mortality was 1.07 (95% confidence interval [CI], .63–1.83) for high-dose colistin. Similar results were obtained when using the study period as the exposure variable, in the subgroup of bacteremic patients (n = 207) and in the propensity-matched cohort (OR, 1.11 [95% CI, .67–1.82]). Nephrotoxicity (RIFLE injury or higher; OR, 2.12 [95% CI, 1.29–3.48]; n = 396) and seizures were significantly more common with high-dose colistin. Conclusions: In a large cohort, we found no association between high colistin dosing and all-cause mortality. High dosing was associated with more nephrotoxicity.